The Discourse of Marriage in the Greco-Roman World - Beneker, Jeffrey (Wisconsin Studies in Classics Ser, 2020)
Intro -- Contents -- List of Illustrations -- Editions and Abbreviations -- Introduction: The Discourse of Marriage and Its Context-Georgia Tsouvala -- Wedding Connections in Greek and Roman Art-Rebecca H. Sinos -- Violence in the Roman Wedding-Karen Klaiber Hersch -- Plutarch's Marriage Advice and the Tradition of the Poetic Epithalamium-Paolo Di Meo -- Epicurus on Marriage-Geert Roskam -- The Impossible Feminism of "Seneca, On Marriage": Style and the Woman in Jerome, Against Jovinian 1-Alex Dressler -- Marriage and Animal Exemplarity in Plutarch-Katarzyna Jazdzewska -- Death Is Not the End: Spousal Devotion in Plutarch's Portraits of Camma, Porcia, and Cornelia-Jeffrey Beneker -- Erotic Desire and the Desire to Marry in the Ancient Greek Novels-Silvia Montiglio -- Contributors -- Index -- Index Locorum.